Penanggulangan Kejahatan Transnational Crime Oleh Ditpolair Polda Sumut Di Wilayah Selat Malaka - Erwin Wijaya Siahaan; Triono Eddy; Alpi Sahari (Universitas Batanghari Jambi, 2021)
The development of a very dynamic strategic environment has resulted in efforts to enforce the law of sovereignty and security at sea, especially in the Malacca strait area from time to time always faced with quite complex challenges. Moreover, if it is related to the geographical constellation of Indonesia in the form of an archipelago with two-thirds of its territory consisting of the sea, its strategic position and the content of potential marine resources. The problems discussed in this thesis are: First, the formulation of legal policies against transnational crime. Second, the prevention of transnational crime in the Malacca Strait area by the Ditpolair Polda North Sumatra. Third, the obstacles in overcoming transnational crime in the Malacca Straits area by the Ditpolair Polda North Sumatra. The research method used in this thesis research consists of research specifications, data sources, data collection techniques and data analysis. The type of research used is normative legal research, namely legal research that uses secondary data sources with an emphasis on theoretical and qualitative analysis which is also referred to as library research or document study. Legal policy formulation, of course, must first begin by looking at the act as a crime by making criminal regulations that contain sanctions for criminals (criminalization). The criminalization of transnational crimes that occur in the waters of the Malacca Strait can be seen in the provisions contained in the legislation by grouping the elements of unlawful acts that can be held criminally responsible for the perpetrators. The criminal provisions contained in the laws and regulations that are formed are essentially for the creation of legal certainty as a legal goal. Legal policy for dealing with transnational crime based on the strategic environment of the Malacca Strait is influenced by several aspects, including geography, demography and natural resources. Border areas in the Malacca Strait that are not supervised, especially water areas, create vulnerability to the theft of natural resources such as illegal fishing. In addition, several border areas and outer islands which are only limited by forest areas also create vulnerability to illegal logging carried out by foreign nationals.